Prolingua se bydrae tot terminologieontwikkeling in Afrikaans - Alberts, Mariëtta (Lexikos, 2017)
Prolingua's Contribution to Terminology Development in Afrikaans.The research problem addressed in this article deals with the isolated development of Afrikaans terminology in a multilingual dispensation. The research problem manifests itself in three ways: the need for such terminology; the sustainability thereof; and whether a single institution, such as Prolingua, could maintain such development. Prolingua, an association for English and Afrikaans language practitioners, was founded in 1950. At the time it was known as the Transvaal Association of Municipal Translators. As the name indicated, the members were mainly municipal officials. Municipal services included several services that, at the time needed bilingual terms for various areas in the workplace. The country's bilingual language policy then required terms to be translated and created for all municipal departments — suddenly there was a need for Afrikaans terms. The aim of the newly established association was, among other things, to translate, create and standardise terminology and to discuss problems with translation. Later more attention was given to terminology-related problems and the association became more inclusive and inviting for language practitioners from other institutions to join its ranks. This article deals with the need for Afrikaans terminology and gives information on the history of Prolingua and its contribution to terminology development in Afrikaans, i.e. the Prolingua term list and other products and services. The contributions made by external collaborators regarding terminology development also receive attention. Prolingua's cooperation with other institutions is discussed. The article concludes with recommendations for a way forward.Keywords: classic origin; collaborator; cooperation; database; digitisation; digitalisation; harmonisation; language policy; language practitioner; neologism; online terminology products; standardisation; technical dictionary; term creation; term list; terminology development; terminology; terminology management system